Memórias da gestão: o percurso da identidade administrativa de tropeiros em Minas Gerais - Gusttavo Cesar Oliveira Lima (2009)
This research paper presents and discusses the tropeiros administrative practice in the 20th century in Minas Gerais based on the study of the identity with this occupation. Tropeirosare, here, defined, as professionals who transported the merchandise and materials with muares (donkeys and mules); in this manner, they used to promote the connection between villages with the commerce of their products and animals (cows or muares). Through the life and professional history of the individuals in this research, this study explains how the everyday activities, linked to the transportation management, took place.With the collected data, it attempts to describe the identity of the commerce with the understanding of the main strategies and tactics connected to the tropeiros practice. The questions related to the social and professional identities involving the socialization aspectwith work and the identification with the professional practice were also analyzed. In this research, in the history of the tropeiros, who are still alive living in different towns in Minas Gerais, it was observed different concepts which coincide with the definition of what is meantto be a tropeiro. These concepts are based on the type of business performed; some tropeiros identified with the cattle commerce, mule commerce, material transport (such as firewood) and commerce of agriculture production merchandise. These types of activitiesprovided important roles in the economies of the villages since they transported and supplied businesses, providing aid to the rural producers in the creation and the disposal of production.The identity of the tropeirismo business was made up based on the practice of management related to the activities of buying, selling, negotiating and interacting among other aspects where the analysis of the identity of this profession was brought forward. An importantaspect distinct in this business refers to the intense practice of relationships based on trust which can be seen in the social aspects, such as family relationships and friendships that are positioned in this activity. The study of the administrative identity of tropeirismo is part ofthe proposal to make it explicit the managerial practice of the past, making an important contribution in the organizational studies. From the history collected, its presented more than facts narrated from the analysis about the tropeiros discourses; it attempts to reconstitute narrative memories pertaining to the end of these activities allowing todemonstrate how the beginning of technology required from the tropeirismo new means of work that the development of the transportation system gave rise to the impossibility to continue the tropeirosactivity.